Big data and personal data: Legal nature and regulatory issues - S. N. Tagaeva; E. M. Gatiyatullina (Цифровое право, 2025)
In the context of the rapid development of digital technologies, the legal regulation of Big Data and concomitant recognition as an object of civil circulation acquires both a theoretical and a practical relevance. The particular significance accorded to the relationship between Big Data and personal data involves the need to balance private and public interests. The work sets out to comprehensively analyze the legal character of Big Data and its relationship with personal data to identify approaches for improving the legal framework in this area. Approaches to establishing a legal regime for Big Data take into account specific aspects of the circulation of personal data and the development of mechanisms for protecting citizens’ rights. Domestic and foreign legislation is contrasted according to the comparative legal method in the light of jurisprudential positions on the legal regulation of Big Data and personal data. Big Data is shown to have a heterogeneous structure that includes not only information but also technical devices and software that enable the collection, processing, and analysis of data. The results of Big Data processing, which represent a property interest for entities involved in civil transactions, can be the subject of civil law contracts. Conflicts between the development of Big Data technologies and existing personal data legislation necessitate the creation of a new legal mechanism for their regulation. For the successful implementation of Big Data technologies, it is necessary to ensure a balance between the protection of personal data and the opportunities for their use in analytical processes. The creation of a new legal mechanism for regulating Big Data must take into account its specific features to ensure a balance between the protection of personal data and the business needs for using such data for analytical purposes.